2022
DOI: 10.1080/21645515.2022.2081024
|View full text |Cite
|
Sign up to set email alerts
|

Safety and clinical efficacy of human rabies immunoglobulin in post exposure prophylaxis for category III animal exposures

Abstract: The human rabies immunoglobulin (HRIG) is a life-saving immune biological essential for all category III animal exposures. It provides neutralizing antibodies at the site of exposure until the body can produce vaccine-mediated antibodies. We conducted this study to determine the safety and clinical efficacy of an HRIG being used presently for post-exposure prophylaxis (PEP) and to strengthen the existing evidence for its further usage. We conducted a prospective cohort study in 123 subjects with category III a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…It can also simplify vaccination, improve compliance, and reduce the cost of rabies vaccination 2 . In addition, Haradanhalli et al’s 4 study provides strong evidence for the safety and clinical efficacy of HRIG in category III animal exposures. According to relevant data reports, the application of HRIG within 1 week of receiving the rabies vaccine will not affect the immune effect of the vaccine to produce protective antibodies, which can provide valuable time for active immunization of the vaccine 5…”
Section: Discussionmentioning
confidence: 99%
“…It can also simplify vaccination, improve compliance, and reduce the cost of rabies vaccination 2 . In addition, Haradanhalli et al’s 4 study provides strong evidence for the safety and clinical efficacy of HRIG in category III animal exposures. According to relevant data reports, the application of HRIG within 1 week of receiving the rabies vaccine will not affect the immune effect of the vaccine to produce protective antibodies, which can provide valuable time for active immunization of the vaccine 5…”
Section: Discussionmentioning
confidence: 99%
“…Human Rabies Immunoglobulin (HRIG) is a life-saving immune biological, particularly necessary for individuals exposed to category 3 animal bites. These bites are characterized by severe wounds with a high risk of rabies transmission, necessitating immediate administration of HRIG (31). HRIG provides immediate protection by supplying neutralizing antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…HRIG provides immediate protection by supplying neutralizing antibodies. Previous studies have shown that these antibodies play a crucial role in bridging the gap until the individual’s immune system can generate vaccine-mediated antibodies (31).…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 ] A combination of anti-rabies immunoglobulin and vaccine has become the standard World Health Organization (WHO) treatment for humans with suspected exposure to rabies virus. [ 5 ] The advances in passive immunoprophylaxis, most notably shift from recommended polyclonal human or equine immunoglobulins to monoclonal antibody therapies. [ 6 ] In 2002, the Strategic Advisory Group of Experts (SAGE) of the WHO recommended that cocktails containing at least two mAbs binding to non-overlapping epitopes of rabies virus G glycoprotein should be encouraged as an alternative to eRIG or hRIG as mAbs can be produced with standardized quality in large quantities, do not use animals in the production process, and have higher effectiveness and reduced risk of adverse events.…”
Section: Introductionmentioning
confidence: 99%